Patterns in the sand - Goldenbaum, Sally (Goldenbaum, Sally. Seaside knitters mystery., 2009)
When young fiber artist Willow Adams visits Izzy Chambers' knitting studio, she's immediately embraced by the Seaside knitters, and they see the monthly arts event at Canary Cove as a perfect place to showcase Willow's work. But the idyllic summer in Sea Harbor turns somber when the body of Nick Peabody - owner of a popular gallery - is found in a garden. Soon Nick's secrets begin to surface, and the residents of Sea Harbor realize they didn't know him at all. And when Nick's will reveals that his entire estate has been left to Willow, the knitters find that Willow has some dark secrets of her own.